Organic-solvent assisted synthesis of highly dispersed iron based Fischer-Tropsch catalysts with MCF support: The effect of organic-solvent. (1st April 2022) - Huang, Siyuan; Liu, Chengchao; Chen, Yao; Hong, Jingping; Lyu, Shuai; Zhao, Yanxi; Zhang, Yuhua; Li, Jinlin
Graphical abstract: Highlights: Organic solvent could influence the dispersion of iron species on MCF support. Ethanol and acetic acid prepared catalyst showed the better carbonization abilities. Ethanol prepared catalyst exhibited the high FTY values of 4.68 mol·/(g Fe s)·10 −5 . The ɛ-Fe2 C sustained for 100 h test at 270 °C as the dominant phase. Abstract: The development of efficient catalysts for Fischer-Tropsch synthesis has attracted much attention in recent years. Mesoporous cellular silica foams (MCFs) supported iron-based Fischer-Tropsch catalysts are prepared via the organic solvent-assisted impregnation methods. The organic solvents (ethanol, acetic acid, glucose, and citric acid) have a great impact on both the structure and performance of the catalysts. In the case of catalyst Fe/MCF-E, obtained by ethanol-assisted impregnation, forming a highly dispersed ɛ-iron phase supported on the supports during relevant industrial FTS process, exhibited excellent stability and activity for 100 h. The Fe/MCF-E catalyst showed C2 -C4 olefin selectivity of 30.9% and FTY (iron-time-yield) of 4.68 mol/(gFe · s)·10 −5 at 270 °C, and achieved a total olefin selectivity of 48.6% and FTY of 38.59 mol/(gFe · s)·10 −5 at 300 °C. These results highlight a convenient strategy to prepare highly stable and active MCF-supported iron based catalysts for FTS.